Application of the Flipped Classroom model in the learning of the superior mathematics course - César Vallejo of Chiclayo University, 2016 - Zuñe Chero, Limberg (2018)
The general aim of this research work was to apply the Flipped Classroom Model in the learning of the Superior Mathematics course. Methodologically it is framed in a descriptive, analytical and pre-experimental design study, taking as sample the students of the II Cycle, section C, of the Professional School of Administration of the César Vallejo University affiliate Chiclayo, for the Measurement of the variables of study was used as an Instrument of data collection of the UN Questionnaire with Likert scale of type which was validated by expert judgment and whose reli-ability I throw a 0.805 on the coefficient of Cronbach's alpha. The results of the application of the Flipped Class mod-el showed that the methodology applied, as well as the complementary means and materials in the teaching practice; as well as the improvement of the learning of the superior mathematical course, in which the students show the degree of satisfaction for the development of the collaborative work. Among the conclusions it is highlighted that the appli-cation of the model was invented as an innovative methodology; likewise, the results in the evaluation of the appren-ticeships showed the majority approval of the students in the Superior Mathematics course.